Zróżnicowanie poziomu rozwoju gospodarczego województw w Polsce a wielkość migracji międzywojewódzkich - Dańska-Borsiak, Barbara (Differentiation of the Economic Development of Polish Voivodships and its Influence on the Level of Inter-Voivod Ship Migration, 2008)
The aim of the paper is to show the differences in the level of Polish voivodships' economic development, to prove that these differences affect the level of inter-voivodship migration and to enumerate and measure the main economic factors which influence people's migration decision. In the first part of the paper the taxonomic measure of development is calculated. The aim is linear ordering of voivodships, according to some variables, being the determinants of the economic development level. Then groups of voivodships similar according to the above mentioned variables are separated. In the last part econometric models are used to specify the factors that affect the level of inter-voivodship migration.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 364-370